Exploring Chinese secondary students’ behaviors towards online homework based on the UX model: does homework completion relate to academic performance? - Chen, Liu; Wong, Su Luan; Zeng, Shaoning; How, Shwu Pyng (Elsevier, 2024)
The benefits of online homework are widely acknowledged for student learning. Numerous studies have provided evidence supporting the notion that the completion of an adequate amount of traditional homework is associated with enhanced academic success. However, there are inconsistent conclusions on the effect of homework completion on academic performance among the students who were exposed to online homework, particularly in China. In order to explore the behaviors of Chinese secondary students towards online homework, a correlational analysis is employed to determine the relationship between homework completion and academic performance among 103 students from China. Findings suggest a positive yet moderate association between online homework completion and academic performance. A follow-up qualitative interview with 10 purposefully selected students, based on the UX model by Topolewski, Krawczyk, Pallot & Huotari (2020), reveals that the cognitive and emotional factors are most influential on their behaviors towards online homework. Further studies are recommended to delve into the factors influencing students’ intention to engage with online homework. Additionally, limitations of this study are outlined.